Gaine's New York Pocket Almanac for 1787.
Printed almanac with manuscript notes by an unknown person relating to wages paid by and hours worked for William H. Ledon, and to a marriage between Nathaniel Fitch and Caty Groat.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Almanacs; Ledon, William H; Fitch, Nathaniel; Fitch, Caty Groat